The global, regional and national burden of pancreatitis due to alcohol use: Results from the Global Burden of Disease Study 2021 and projections to 2040 - Letai Li; Yaowen Zhang; Jiajie Leng; Siyu Li; Yang Lei; Zhenrui Cao; Yuxiang Luo; Haibing Xiong; Zhongjun Wu; Rui Tao; Yingjiu Jiang (PLoS ONE, 2025)
Background Alcohol use is a major risk factor for pancreatitis and global mortality. Despite its impact, comprehensive analyses of the burden across regions and sociodemographic strata remain scarce. This study examines global trends (1990–2021) and projects future burdens to 2040. Method Data on Deaths and Disability-Adjusted Life Years (DALYs) attributable to alcohol-induced pancreatitis were retrieved from the 2021 iteration of the Global Burden of Diseases (GBD) database. Trends were analyzed, Age-Period-Cohort models quantified age, period, and cohort effects on Age-Standardized Mortality Rate (ASMR) and Age-Standardized Disability-Adjusted Life Year (ASDR). Associations with SDI were evaluated, burden decomposition applied, and projections made to 2040. Results Globally, both age-standardized death rate (ASDR) and mortality ratio (ASMR) exhibited overall declines (EAPC for ASDR: −0.32%; ASMR: −0.27%), but the reduction was significantly smaller in males (ASDR-EAPC: −0.18%) compared to females (−1.34%). Notablly,Eastern Europe had the highest burden (ASDR: 64.03), High-income Asia-Pacific saw the largest declines (EAPC for ASDR: −2.45%; EAPC for ASMR: −2.96%), while Southeast Asia experienced the fastest increase (EAPC for ASDR: 1.98%; EAPC for ASMR: 2.13%). ASDR peaked at ages 45–49, with high-middle SDI countries showing the highest values. Period and cohort effects varied by SDI, with downward trends in high SDI countries and upward trends in lower SDI groups. Population growth and aging drove increases in deaths and DALYs, while epidemiologic changes reduced them. By 2040, deaths and DALYs will stabilize, ASMR will decline until 2034 then rise, and ASDR will decrease until 2035 then increase, driven by population growth. Conclusion Alcohol-related pancreatitis burden demonstrates striking gender, age, and geographic heterogeneity. Targeted policies for high-risk groups (middle-aged/elderly males) and regions (Eastern Europe, Low-middle SDI countries), coupled with preparedness for aging-related burden escalation, are urgently needed.